Menggagas Tafsir Anti Trafficking (lnterpretasi Historis terhadap Q.S. al-Nur: 33) - Syarif, Ali Imron (Sunan Kalijaga State Islamic University & The Asia Foundation, 2006)
This article discusses about woman sexual exploitation according to the Qur'an. The study focuses on the general Qur'anic massages on human and women's rights, and, more specifically, an-Nur: 33. It is obvious that since the beginningof its revelation, the Qur'an has been strongly against woman sexual exploitation. It, gradually and proportionallyacknowledges women's rights. Woman trafficking is in opposition to the spirit and elan vital of the Qur'an.